Constrained Spline approximation - Nada Zuhair Abd AL-Sada (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper, we find  the relationships between the order of constrained approximation by a polynomials which is copositive with a   function  by modulus of smoothness    , to the function   ,which is multiply by  , and between the best approximation to the pairs of intertwining splines of a polynomials  in  and the same of  relationships but by the modulus of smoothness    to the function  multiply by    . Also we find the order of constrained approximation to the pairs of intertwining polynomials in